E-Report Application: The Role of Stakeholders in The Assessment System in Schools - Jamalia, Jamalia; Huriyah, Lilik; Yuliati, Wiwik (JURNAL AL-TANZIM, 2022)
This study aims to find out about the role of school stakeholders in processing student grades using the e-report application. This study uses a descriptive method with a qualitative approach, namely observation by observing the website and using the website directly. Interviews were conducted with informants regarding the use of applications and documentation of reports issued from applications to school stakeholders who now participate in the use of e-reports. The data analysis technique was carried out using data reduction, data presentation, and concluding. The results show that the role of school stakeholders in the use of interconnected e-reports starts from the administrative field in data collection, teachers in data entry, curriculum fields in checking data, and BP teachers who enter student attendance to get to the parents. The existence of this E-report application shows the discipline and perseverance of the stakeholders in controlling IT. The processing of the scores on this e-report will also be copied into the student's master book, and later the results of this assessment will be submitted to the Surabaya City Education Office for nomination with other schools.